2017
DOI: 10.1097/md.0000000000005856
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided pulsed radiofrequency treatment of the cervical sympathetic chain for complex regional pain syndrome

Abstract: The stellate ganglion is a common target to manage neuropathic pain in the upper extremities. However, the effect duration of a single stellate ganglion block is often temporary. To overcome the short-term effects of a single sympathetic block, pulsed radiofrequency (PRF) can be applied. The aim of the present study was to investigate the efficacy of PRF on the cervical sympathetic chain under ultrasound guidance for complex regional pain syndrome (CRPS).Twelve CRPS patients who underwent PRF on the cervical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…[6] Additionally, the effect range of the EM field is much smaller than that of a few milliliters of local anesthetic. [9] Therefore, when performing PRF, it is ideal to position the needle tip as close as possible to the target nerve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] Additionally, the effect range of the EM field is much smaller than that of a few milliliters of local anesthetic. [9] Therefore, when performing PRF, it is ideal to position the needle tip as close as possible to the target nerve.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Although PRF is increasingly used to treat various pain conditions, [7] its application to sympathetic nerve has been rarely reported. [8,9] We previously reported our clinical experience using PRF on the cervical sympathetic chain (CSC PRF). [9] However, there are no published reports on the application of PRF to the TSG (TSG PRF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 This has been supported by several previous studies reporting that local anesthetic blockade of the sympathetic chain effectively controlled CRPS symptoms. [51][52][53] Furthermore, persistent noxious input resulting from nerve damage increases the excitability of nociceptive neurons in the spinal cord, referred to as central sensitization. 54 Central sensitization results in hyperesthesia, allodynia, and hyperalgesia.…”
Section: Pathophysiology Of Complex Regional Pain Syndromementioning
confidence: 99%
“…Additionally, several previous studies have found that repeated sympathetic blockade with local anesthetics can attenuate CRPS symptoms. [51][52][53] In refractory cases of CRPS, spinal cord stimulation was found to have potential to relieve such symptoms. 64 In addition to the aforementioned medications and procedures, combined treatment with active or passive mobilization, massage, contrast baths, and transcutaneous electrical nerve stimulation have been used as adjunctive therapies to help manage CRPS, although data regarding efficacy are limited.…”
Section: Treatment Of Complex Regional Pain Syndromementioning
confidence: 99%